Improving Students’ Ability In Formulating Research Introduction Through Scientific Approach - Marpaung, Tiarma Intan; Purba, Christian Neni; Lumbangaol, Dameasi Bulan (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
This classroom action research was conducted to solve the students’ difficulties in designing a research introduction by applying scientific approach. The subjects were the sixth semester students of English Department of Teacher Training and Education Faculty of HKBP Nommensen University Indonesia who took Writing Research Paper subject. There were 30 students and they were organized into 8 groups. This research occupied 2 cycles which involved 4 steps (planning, acting, observing, and reflecting) for each cycle. The findings showed that using scientific approach has successfully developed the students’ ability in designing introduction of a research. The development derived from the increasing of students’ mean score in pre-cycle (54), first cycle (67.73), and second cycle (77,5). The students’ difficulties (fail to identify problems of research, decide research title and determine technique of solving the problem) were also decreased significantly after the second cycle had been conducted.